Human Resource Readiness in Implementing the Srikandi Application (Case Study: South Sumatra Provincial Archives Service) - Ahmad Royhan Habibillah; Nyimas Nur Andini; Andries Lionardo (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to analyze the level of human resource (HR) readiness in implementing the Integrated Dynamic Archival Information System (SRIKANDI) application at the South Sumatra Provincial Archives Office. The approach used was descriptive qualitative research with data collection techniques through in-depth interviews, observation, and documentation. The analysis was conducted using the E- Readiness theoretical framework from the Harvard Kennedy School combined with the People dimension of the STOPE Framework. The results of the study indicate that HR readiness is in the transitional or fairly ready category, with three main dimensions being examined: support, capacity, and value. From the support aspect, implementation has been supported by hierarchical regulations from the central to regional governments. From the capacity aspect, some employees have been able to operate the application, although there is still a gap in digital competency among employees. From the value aspect, the SRIKANDI application has been proven to increase administrative efficiency and encourage a transformation of work culture towards electronic-based governance. Supporting factors include the development of digital competencies, employee openness to technology, and leadership support. Inhibiting factors include the disparity in digital capabilities among employees, dependence on non-civil servants, and limited internal information technology experts.